2006
DOI: 10.1063/1.2397006
|View full text |Cite
|
Sign up to set email alerts
|

Ti O 2 anatase nanolayer on TiN thin film exhibiting high-speed bipolar resistive switching

Abstract: The surface oxidized layer of a TiN barrier metal thin film grown on a Pt electrode was used as a resistive switching material. The fabricated memory cell shows bipolar resistive switching on a nanosecond order. A TiO2 anatase layer of about 2.5nm thick on TiN thin film was characterized by high-resolution scanning transmission electron microscopy. The results suggested that the high-speed resistive change was derived from the Mott transition in the TiO2 anatase nanolayer, and the obtained results could relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
122
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(127 citation statements)
references
References 19 publications
4
122
0
1
Order By: Relevance
“…The reproducible RS is achieved by repeating SET and RESET processes. Although the RS phenomena and their reproducibility were reported and there are many analogical reasoning of reversible RS in metal oxides 2,9,11,12,[14][15][16][17][18][19][20][21][22][23][24] , their switching mechanism has not yet been clarified. To reveal the RS mechanism, direct observations of conducting filaments are required.…”
Section: Introductionmentioning
confidence: 99%
“…The reproducible RS is achieved by repeating SET and RESET processes. Although the RS phenomena and their reproducibility were reported and there are many analogical reasoning of reversible RS in metal oxides 2,9,11,12,[14][15][16][17][18][19][20][21][22][23][24] , their switching mechanism has not yet been clarified. To reveal the RS mechanism, direct observations of conducting filaments are required.…”
Section: Introductionmentioning
confidence: 99%
“…Mott transition is also proposed as the mechanism for the bipolar resistive switching observed in a 2.5 nm anatase TiO 2 layer grown by oxidation of a TiN diffusion barrier [48,49]. Mott transition may be triggered by the increase in donor concentration caused by the electron injection from the top electrode (Pt), which is accompanied by oxygen vacancy formation and O 2 migration in the anatase TiO 2 layer.…”
Section: Resistive Switching Induced By Mott Transitionmentioning
confidence: 99%
“…The reported values of switching parameters of the Mott transition devices discussed above are summarized in Table 9.1 [19,46,48,49,[51][52][53].…”
Section: Resistive Switching Induced By Mott Transitionmentioning
confidence: 99%
“…High-resolution scanning transmission electron microscopy characterization of TiO2 anatase nanolayer of about 2.5 nm thick on TiN thin film suggested that the resistive change was due to the Mott transition in the TiO2 anatase nanolayer which could relate to the formation of filament paths. 25) From different switching behaviors of Pt/TiO2/Pt and Ir(O)/TiO2/ Pt, the mechanism of resistance switching of TiO2 thin films was suggested to be local rupture and recovery of conducting filaments near the anode interface. 27) Further study indicated that only small part of the conducting filaments in the thin films near the anode contributed to the resistance switching.…”
Section: Tio 2 Zro 2 and Hfo 2 Thin Filmsmentioning
confidence: 99%